Opening Address - Cartwright, Silvia (Victoria University of Wellington Law Review, 2002)
The Honourable Dame Silvia Cartwright, Governor-General of New Zealand, provides a brief introduction to Sir Ivor Richardson’s legal career and his impact as a judge of the Court of Appeal. She lauds Sir Ivor’s influence on the evolution of New Zealand law as a watcher, protector and developer of the law.